The black book of outsourcing : how to manage the changes, challenges, and opportunities - Brown, Douglas, 1959- (John Wiley & Sons, 2005)
The Black Book of Outsourcing is a comprehensive guide and directory for the emerging field of outsourcing, including expert advice on how to operate an outsourcing program, how to deal with the political aspects of outsourcing, and how to find a career in outsourcing.